Independent and combined associations of sleep duration and sleep quality with common physical and mental disorders: Results from a multi-ethnic population-based study - Seow, Lee Seng Esmond; Tan, Xiao Wei; Chong, Siow Ann; Vaingankar, Janhavi Ajit; Abdin, Edimansyah; Shafie, Saleha; Chua, Boon Yiang; Heng, Derrick; Subramaniam, Mythily (PloS one, 2020)
Sleep duration and sleep quality are often linked to increased risk of mortality and morbidity. However, national representative data on both sleep duration and sleep quality and their relationship with chronic health problems are rarely available from the same source. This current study aimed to examine the independent and combined associations of sleep duration and sleep quality with physical and mental disorders, using data from the Singapore Mental Health Study 2016. 6,126 residents aged [greater than or equal to]18years participated in this epidemiological, cross-sectional survey. Sleep measures were assessed using the Pittsburg Sleep Quality Index while lifetime or 12-month medical and psychiatric diagnoses were established using the Composite International Diagnostic Interview 3.0. Both short sleep (<6hrs compared to 7-8hrs) and poor sleep were found to be independently associated with chronic pain, obsessive compulsive disorder and any mental disorder while poor sleep was additionally associated with major depressive disorder, bipolar disorder, generalized anxiety disorder and any physical disorder, when adjusted for confounders. Poor sleep combined with short sleep ([less than or equal to]6hrs/day vs 7-8hrs/day) was associated with the highest number of comorbidities among other sleep combinations. Sleep duration and sleep quality, when adjusted for each other, remained independently associated with both physical and mental disorders. Affective disorders may be more closely related to poor sleep quality compared to abnormal sleep duration. Our findings suggest sleep quality to be a more important indicator for psychological and overall health compared to sleep duration.